Inclusion complexation of pinostrobin with various cyclodextrin derivatives - Jintawee Kicuntod (2018)
© 2015 Elsevier Inc. All rights reserved. Pinostrobin (PNS) is one of the important flavonoids and can be abundantly found in the rhizomes of fingerroot (Boesenbergia rotrunda) and galangal (Alpinia galangal and Alpinia officinarum), the herbal basis of Southeast Asian cooking. Similar to other flavonoids, PNS exhibits anti-oxidative, anti-inflammatory and anti-cancer properties. However, this compound has an extremely low water solubility that limits its use in pharmaceutical applications. Beta-cyclodextrin (βCD) and its derivatives, 2,6-dimethyl-βCD (2,6-DMβCD) and the three hydroxypropyl-βCDs (2-HPβCD, 6-HPβCD and 2,6-DHPβCD), have unique properties that enhance the stability and solubility of such low-soluble guest molecules. In the present study, molecular dynamics simulations were applied to investigate the dynamics and stability of PNS inclusion complexes with βCD and its derivatives (2,6-DMβCD, 2,6-DHPβCD, 2-HPβCD and 6-HPβCD). PNS was able to form complexes with βCD and all four of its derivatives by either the chromone (C-PNS) or phenyl (P-PNS) ring dipping toward the cavity. According to the molecular mechanics-generalized Born surface area binding free energy values, the stability of the different PNS/βCD complexes was ranked as 2,6-DHPβCD > 2,6-DMβCD > 2-HPβCD > 6-HPβCD > βCD. These theoretical results were in good agreement with the stability constants that had been determined by the solubility method.